Analisis Sulfur (S) dan Besi (Fe) pada Limbah Cair Panas Pembangkit Listrik Tenaga Uap (PLTU) Di Kelurahan Panau Kecamatan Palu Utara - Madjid, Nurhidayah Abd.; Napitupulu, Mery; Said, Irwan (Universitas Tadulako, 2018)
This research aims to find the levels of sulfur and iron in the liquid waste heat of PLTU discarded into bodies of water at Panau village Subdistrict north of Palu. This research used spectrodirect for the analysis. The result of the research showed that the waste not contents the sulfur or iron, but contents the sulfite. Based on measurements using wavelengths of 405 nm was found that the sample contains 3.12 mg/L sulfite compounds.